IMPLEMENTASI MANAJEMEN AKADEMIK FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JABAL GHAFUR SIGLI - Syahwal, Murniati AR, Bahrun (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
Abstract: Academic management has a very important role in improving the academic services. Through planning, an effective and efficient academic implementation and monitoring will create a productive work system. The purpose of this study was to determine the academic planning, academic Implementation, monitoring and obstacles in the implementation of academic at the Faculty of teacher Training and Education. The method used was descriptive method with qualitative approach. The techniques of data collection used in this study were documentation, observation, and interviews. The Subjects for this study were Dean, Vice Dean for Academic Affairs, and Head of Administration of the Faculty, Head of Academic Affairs of Faculty and Staff of Academic Affairs of study programs, lecturers and students in the faculty. The results showed that: (1) Academic Planning was implemented by using button up pattern, academic activities was based on academic needs in the Faculty of teacher Training and Education of Jabal Ghafur University of Sigli. The Academic planning activities was started before the beginning of the year, and the preparation of the academic planning for one and another year did not all at once, as well as involve all those who were responsible for the academic. (2) The academic implementation has generally been carried out effectively and efficiently, the implementation of the academic done were management academic personnel resources, time management, facilities and infrastructure management and student services, but in the process of implementation still had many obstacles because of the availability of support facilities, the ability of academic staff as well as the availability of personnel. (3) The Supervision is carried out internal and external, this is to ensure the least accomplished academic planning, and is based on the results of monitoring there are several factors and constraints in the implementation of academic planning, namely internal and external factors.Keywords: Academic Management and Colleges Abstrak: Manajemen akademik memiliki peranan yang sangat penting dalam meningkatkan layanan akademik. Melalui perencanaan, pelaksanaan dan pengawasan akademik yang efektif dan efisien akan menghasilkan sistem kerja yang produktif. Tujuan penelitian ini untuk mengetahui Perencanaan akademik, pelaksanaan akademik, pengawasan akademik dan kendala-kendala dalam pelaksanaan akademik Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur Sigli. Metode penelitian yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan dalam penelitian ini ialah: wawancara, observasi, dan dokumentasi. Subjek penelitian terdiri atas Dekan, Pembantu Dekan Bidang Akademik, Kepala Tata Usaha Fakultas. Kepala SBAK Fakultas, Staf SBAK Jurusan, Dosen dan mahasiswa di fakultas tersebut. Hasil penelitian menunjukkan bahwa: (1) Perencanaan akademik dilaksanakan dengan menggunakan pola button up, kegiatan akademik disusun berdasarkan kebutuhan, kegiatan perencanaan dimulai dari awal tahun, dan penyusunan perencanaan untuk satu tahun dan tahun berikutnya dilakukan tidak sekaligus, serta melibatkan semua personil yang bertanggungjawab terhadap bidang akademik. (2) Pelaksanaan akademik, secara umum telah dilaksanakan melalui pengelolaan sumber daya akademik, pengelolaan waktu, pengelolaan sarana dan pengelolaan pelayanan mahasiswa, namun dalam proses pelaksanaannya masih ada berbagai kendala, karena ketersediaan fasilitas pendukung, kemampuan staf akademik serta ketersediaan personalia yang mengelola masih relatif kurang. (3) Pengawasan yang dilaksanakan secara internal dan eksternal, hal ini untuk memastikan terlaksana tidaknya perencanaan akademik, dan berdasarkan hasil pengawasan ada beberapa faktor kendala dalam pelaksanaan dan perencanaan akademik yaitu faktor internal dan eksternal.Kata Kunci: Manajemen Akademik dan Perguruan Tinggi